Investigation and evaluation of the solar air collector model to support the solar vortex engine - Mustafa, A.T. (Asian Research Publishing Network, 2015)
In this study, mathematical and experimental models were implemented for circular solar air collector. Modeling methodology with conservation equations of continuity, momentum and energy were presented, and model solution is obtained by utilizing a developed code in MATLAB program. An experimental model of concentric circles with outer and inner diameters of 8.8 m and 1.0, respectively, was designed and fabricated in order to perform measurements for the thermal and flow processes in the system. The canopy was inclined by 8.5Â°. The results showed that, at same solar irradiation, the temperatures of air flow, canopy and ground are increasing by decreasing the radius. When the canopy slope increases, air flow temperature decreases and canopy temperature increases for a constant solar radiation. When the solar radiation increases, air flow, canopy and ground temperatures increases for the same collector radius. The validations of the model predictive and therefore comparisons with results of experimental model of this study and Manzanares prototype data have been done. The model results agree with the experimental results. Further investigations are recommended after installation of the vortex generation engine where the residence time of the air particles will be changed, and consequently the air stream temperature and velocity are expected to change, as well. Â© 2006-2015 Asian Research Publishing Network (ARPN).